2012
DOI: 10.7314/apjcp.2012.13.4.1361
|View full text |Cite
|
Sign up to set email alerts
|

Screening Colonoscopy from a Large Single Center of Thailand - Something Needs to be Changed?

Abstract: Background: Results of screening colonoscopy from Western countries reported adenoma detection rates (ADRs) of 30-40% while those from Asia had ADR as low as 10%. There have been limited data regarding screening colonoscopy in Thailand. The objectives of this study were therefore to determine polyp and adenoma detection rates in Thai people, to evaluate the incidence of colorectal cancer detected during screening colonoscopy and to determine the endoscopic findings of the polyps which might have some impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
3
19
2
2
Order By: Relevance
“…Researchers from Asian-pacific developed countries have also reported a significant increase of CRC over the last decades. It seems that these countries actually have the same incidence as western countries; this could be due to the "westernization" of lifestyles in these countries (Choe et al, 2007;Chung et al, 2010;Aswakul et al, 2012;Ng and Wong 2013;Yang et al, 2014). This discrepancy between our findings and theirs might be related to lifestyle, diet, younger population and also genetic differences.…”
Section: Discussioncontrasting
confidence: 51%
“…Researchers from Asian-pacific developed countries have also reported a significant increase of CRC over the last decades. It seems that these countries actually have the same incidence as western countries; this could be due to the "westernization" of lifestyles in these countries (Choe et al, 2007;Chung et al, 2010;Aswakul et al, 2012;Ng and Wong 2013;Yang et al, 2014). This discrepancy between our findings and theirs might be related to lifestyle, diet, younger population and also genetic differences.…”
Section: Discussioncontrasting
confidence: 51%
“…This finding was in contrast with the study by Aswakul et al, 2012 that showed only 2.6% of polyps were advanced.…”
Section: Discussioncontrasting
confidence: 97%
“…Also, about 14% of the polyps in an Iranian study by Zare-Mirzaie et al, 2013 had high-grade dysplasia. Like the study by Aswakul et al (2012), the present research found no relationship between advanced adenoma and sex and age. Likewise, Zare-Mirzaie et al (2013) reported no relationship between sex and age on the one hand and high-grade dysplasia on the other.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Many have discussed the variation in sensitivity and specificity of CTC results when compared to the Colonoscopy. CTC mainly fails in identifying the smaller lesions of <5mm (Aswakul et al, 2012). Colonoscopy overtakes CTC in highly risk population as CTC fails for smaller lesions (Broadstock, 2007).…”
Section: Comparison Between Ctc and Colonoscopymentioning
confidence: 99%